2019
DOI: 10.1186/s13099-019-0336-3
|View full text |Cite
|
Sign up to set email alerts
|

Hypervirulent clade 2, ribotype 019/sequence type 67 Clostridioides difficile strain from Japan

Abstract: BackgroundClostridioides difficile ribotype (RT) 019/sequence type (ST) 67 strains belong to a hypervirulent lineage closely related to RT027/ST1; however, limited data are available for hypervirulent clade 2 lineages in Japan. Herein, we report the draft genome of a C. difficile strain B18-123 belonging to clade 2, RT019/ST67 for the first time in Japan.ResultsThe pathogenicity locus carried by B18-123 (19.6 kb) showed higher homology (97.29% nucleotide identity) with strain R20291 (RT027/ST1) than the refere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…For example, while most isolates of ST13 (60%), ST42 (80%) and ST2 (66.7%) were non-producers, most (75%) isolates of ST6 were moderate producers and most of ST104 (57.1%) isolates were strong producers. One isolate which belong to ST43 (mean OD 570 = 2.22) produced a biofilm as strong as the control 630 strain which belong to ST54 ( Saito et al, 2019 ). Two other isolates that belong to ST8 and ST239 had a stronger biofilm production capacity, compared to the control strain (mean OD 570 = 3.93 and 3.34, respectively).…”
Section: Resultsmentioning
confidence: 97%
“…For example, while most isolates of ST13 (60%), ST42 (80%) and ST2 (66.7%) were non-producers, most (75%) isolates of ST6 were moderate producers and most of ST104 (57.1%) isolates were strong producers. One isolate which belong to ST43 (mean OD 570 = 2.22) produced a biofilm as strong as the control 630 strain which belong to ST54 ( Saito et al, 2019 ). Two other isolates that belong to ST8 and ST239 had a stronger biofilm production capacity, compared to the control strain (mean OD 570 = 3.93 and 3.34, respectively).…”
Section: Resultsmentioning
confidence: 97%
“…Despite having a variant TcdB, 5757-ST67 produced an elevated inflammatory response and alteration of biochemical markers that could be explained by toxin overproduction [ 32 ]. Moreover, mutations in treR (trehalose repressor), CpG depleted genomes [ 31 ] and a PaLoc rather similar to that of strain R202091-ST01 [ 33 ] have been described in this ST, all of which are characteristics of hypervirulent C. difficile strains.…”
Section: Discussionmentioning
confidence: 99%
“…Clostridium difficile infection or known as CDI has been recognized as a typical HAIs and contributes to a significant proportion of morbidity and mortality among hospitalized patients with case-fatality rates of multiple infections varying from mild diarrhea to pseudomembranous colitis (PMC), especially in the elderly patients on antibiotic treatment. [1][2][3][4][5] In addition, the high health costs associated with CDI increase the government's financial burden on health spending. It was noted that half a million infections were associated with CDI in the United States in 2011 with an incidence rate of 8.75 cases/1,000 adult admissions in 2009.…”
Section: Introductionmentioning
confidence: 99%
“…It was noted that half a million infections were associated with CDI in the United States in 2011 with an incidence rate of 8.75 cases/1,000 adult admissions in 2009. 1 In study of Saito et al, 2019 reported the results of C. difficile ribotyping without information on the prevalence or incidence of CDI in Japan. 2 The incidence of CDI increased from 1.7/1,000 to 2.7/1,000 adults in Korea and 17.1/10,000 hospitalized patients in Shanghai were associated with CDI.…”
Section: Introductionmentioning
confidence: 99%